Identification of an immunoglobulin Fc receptor of Actinobacillus actinomycetemcomitans. - Mintz, K P (1994)
Actinobacillus actinomycetemcomitans expresses proteins that bind to the Fc portion of immunoglobulins. The immunoglobulin Fc receptors on the surface of A. actinomycetemcomitans were detected by the binding of biotinylated human or murine Fc molecules to strain SUNY 465 adsorbed to the bottom of microtiter wells. Biotinylated Fc binding was inhibited by unlabeled Fc molecules and human plasma. Fc receptors were identified by the binding of biotinylated Fc molecules to bacterial membrane proteins separated by polyacrylamide gel electrophoresis and transferred to nitrocellulose. Multiple bands were identified, and the major Fc-binding protein was determined to be a heat-modifiable protein. This protein migrated with approximate molecular weights of 25,000 and 32,000 (unheated and heated, respectively). Amino-terminal sequence analysis of this protein revealed a sequence identical to the heat-modifiable protein described for A. actinomycetemcomitans ATCC 43718. This protein sequence exhibits significant homology with the N termini of outer membrane protein A (OmpA) of Escherichia coli and related OmpA-like proteins from other gram-negative bacteria.